Therapeutic effects of Medicago sativa against cyclophosphamide-induced toxicity in rats - Vajihe Rouki; Mohammad Hossein Boskabady; Narges Marefati; Reyhaneh Sotoudeh; Zahra Gholamnezhad (Avicenna Journal of Phytomedicine, 2024)
Objective: Medicago sativa (M. sativa) has been traditionally used for treating anemia; therefore, M. sativa hydro-ethanolic extract therapeutic effects against cyclophosphamide (CP) -induced hematologic and liver toxicity were examined. Materials and Methods: Thirty male Wistar rats were randomly divided to control (saline); CP (100 mg/kg, day 1-3, subcutaneously); CP+ M. sativa 200 mg/kg (MS 200); CP+ M. sativa 400 mg/kg (MS 400); CP+ dexamethasone (0.1 mg/kg), (all groups n=6). Treated animals received M. sativa or dexamethasone by gavage from days 7-14. On days 0, 7, and 14, hematologic parameters, and on the 14th day, serum and liver tissue oxidative stress markers including nitric oxide, malondialdehyde (MDA) and total thiol levels, superoxide dismutase (SOD) and catalase (CAT) activities, serum lipids, and liver enzymes were measured.Results: Animal weight, platelet, white blood cells, and red blood cells counts, hemoglobin and hematocrit as well as thiol, SOD, and CAT activities in serum and liver tissue were significantly reduced, but serum nitric oxide, MDA, total cholesterol, triglycerides, low-density lipoproteins levels, and liver enzymes were increased in the CP group compared to the control group (p<0.05 to p<0.001). Administering M. sativa extract (400 mg/kg) significantly enhanced platelet count, and SOD and CAT activities and inhibited all of the CP toxic effects, while dexamethasone improved platelet count and oxidative stress markers compared to the CP group (p<0.05 to p<0.001).Conclusion: The extract of M. sativa (400 mg/kg) showed therapeutic effects against the CP-induced myelosuppression and thrombocytopenia and improved oxidative stress markers which were comparable to the effect of dexamethasone.